Coccolithophore relative abundances at the Ideale Section - Montalbano Jonico, Southern Italy - Patrizia Maiorano (PANGAEA, 2021)
In the present dataset we provide relative abundance (%) of the main taxa of the coccolithophore. Slides for coccolithophore analysis were prepared following Flores and Sierro (1997). Quantitative analyses were performed at University of Bari, Italy, using a polarized light microscope at 1000 exttimes magnification. Abundances were determined by counting at least 500 coccoliths of all sizes. We also provide estimate of reworked calcareous nannofossils, i.e. taxa belonging to older (Mesozoic and Paleogene-Neogene) stratigraphic intervals, estimated separately during this counting. Warm-water coccoliths include the following taxa: Umbilicosphaera sibogae s.l., Calciosolenia spp., Discosphaera tubifera, Rhabdospaera clavigera, Umbellosphaera spp., Oolithotus spp. The coccolith dissolution index (DI) was estimated according to the following ratio: DI = small Gephyrocapsa/(small Gephyrocapsa + Calcidiscus leptoporus). High values of DI indicate good preservation. Species dominance of the coccolithophore assemblage has been obtained using PAleontological STatistics Software 4.02 (Hammer et al., 2001) and is equivalent to 1-Simpson index.